Extraction of Caffeine from Korean Green Tea - Jin, Y.; Xuan, Y.H.; Jin, Y.S.; Shin, Y.K.; Lee, K.J. (Asian Journal of Chemistry, 2010)
The extraction of caffeine from Korean green tea was performed by various extraction methods such as dipping, stirring, ultrasonic and supercritical CO2 extraction. The extracts were analyzed by reversed-phase high performance liquid chromatography (RP-HPLC). From the experimental results, the amount of caffeine extracted by supercritical CO2 extraction using water as co-solvent was 2 times larger than that by all of the different extraction methods applied.